Iron(III)-promoted hydrofunctionalization/bicyclization of 1, 7-enynes toward benzo[a]fluoren-5-ones. Issue 7 (13th February 2020) - Huang, Min-Hua; Hong, Yu; Hu, Jian-Qiang; Yang, Shi-Zhao; Zhu, Yi-Long; Wang, De-Cai; Jiang, Bo
Graphical abstract: Highlights: A new hydrofunctionalization/bicyclization of C(sp 3 )-tethered 1, 7-enynes is established. The mechanism involves a hydrogen radical induced 6- exo-dig /5- endo-trig bicyclization cascade. This method provides a new entry for the formation of benzo[ a ]fluoren-5-ones. Abstract: A new hydrofunctionalization/bicyclization of C(sp 3 )-tethered 1, 7-enynes toward benzo[ a ]fluoren-5-ones with good to excellent yields has been developed by using Iron(III)/PhSiH3 system as a hydride donor. This protocol involves a reductive 1, 7-enyne-carboannulation cascade, leading to C(sp 3 )H and CC bond-forming events to rapidly build up tetracarbocyclic complexity. A wide range of functional groups relative to 1, 7-enyne substrates were tolerated well under mild neutral-redox conditions.